2014
DOI: 10.1080/11250003.2014.952356
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional biodiversity variations of meiobenthic and nematode assemblages across an extreme environment: a study case in a Blue Hole cave

Abstract: In this paper we have explored for the first time the biodiversity pattern of the meiobenthic assemblage in a Blue Hole of the Maldivian Archipelago. The cave is characterised by a marked change of the chemical water parameters below 50 m of depth, with a relevant increase in hydrogen sulfide, carbon dioxide, and sulfates (H 2 S, CO 2 and SO 4 2-). Thus, three stations were selected above and two below the chemo-thermocline in order to test the possible effects of the chemical variations on the meiobenthos. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 50 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…We notice that the genera Sabatieria and Metalinhomoeus were present in high abundances in the present study. These genera are tolerant to either organic enrichment and low oxygen contents or heavy metals (Heip et al, 1985;Gyedu-Ababio et al, 1999;Danovaro et al, 2009b;Armenteros et al, 2010;Sandulli et al, 2014;Boufahja et al, 2016). In this regard, several studies reported consistently specific nematodes genera as tolerant to different typologies of ahropogenic impacts (Table 7).…”
Section: Nematode Biodiversity As Indicator Of Ecological Quality Stamentioning
confidence: 99%
“…We notice that the genera Sabatieria and Metalinhomoeus were present in high abundances in the present study. These genera are tolerant to either organic enrichment and low oxygen contents or heavy metals (Heip et al, 1985;Gyedu-Ababio et al, 1999;Danovaro et al, 2009b;Armenteros et al, 2010;Sandulli et al, 2014;Boufahja et al, 2016). In this regard, several studies reported consistently specific nematodes genera as tolerant to different typologies of ahropogenic impacts (Table 7).…”
Section: Nematode Biodiversity As Indicator Of Ecological Quality Stamentioning
confidence: 99%
“…Among the most frequent families found, Xyalidae, Linhomoeidae and Cyatholaimidae show representatives typical of muds rich in detritus and often characterized by anoxic conditions (e.g. Stekhoven, 1950;Heip et al, 1985;Semprucci, 2013;Sandulli et al, 2014). D. fallax, D. hirsutum, T. flevensis and T. setifer (Xyalidae) are among the widespread species in El Bibane together with E. longispiculosus, V. glabra and M. stekhoveni (Thoracostomopsidae, Oncholaimidae and Cyatholaimidae, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Loriciferans are known by two endemic species from two Australian caves (Heiner et al, 2009). Finally, Kinorhyncha is the group of scalidophorans most frequently found in caves (Cruz-Palacin and Masalles, 1986;Janssen et al, 2013;Riera et al, 2018;Sandulli et al, 2014), although only four records are identified to the species level: the marine species Echinoderes dujardinii Claparède, 1863 and Meristoderes macracanthus Herranz, Thormar, Benito, Sánchez and Pardos, 2012 from Mediterranean caves (Dal Zotto and Todaro, 2016;Riedl, 1966), and the cave exclusive species Echinoderes cavernus Sørensen, Jørgensen and Boesgaard, 2000, and Ryuguderes iejimaensis Yamasaki, 2016 from Australia and Japan, respectively (Sørensen et al, 2000;Yamasaki, 2016). The high percentage of undescribed kinorhynchs (Appeltans et al, 2012) and the comparatively high number of records in caves highlights the importance of paying more attention to the kinorhynchs at these habitats as caves might hide important species to understand the evolution of the group.…”
Section: Introductionmentioning
confidence: 99%